The features of profiles of frustrstion reaction of modern teenagers (Actual Problems of Psychology in Educational Institutions, 2022)
There are determined the features of frustration reactions of pupils of teens. The basic parameters of types and directions of frustration reaction of students of middle and senior groups are revealed. It is carried out the system analysis of the tendencies and patterns of frustration reactions of students taking into account age and individual characteristics.